10 Principles for Doing Effective Couples Therapy - Gottman, Julie Schwartz; Gottman, John Mordechai; Siegel, Daniel J., 1957- (New York : W.W. Norton & Company, 2015)
From the country's leading couple therapist duo, a practical guide to what makes it all work. In 10 Principles for Doing Effective Couples Therapy, two of the world's leading couple researchers and therapists give readers an inside tour of what goes on inside the consulting rooms of their practice. They have been doing couples work for decades and still find it challenging and full of learning experiences. This book distills the knowledge they've gained over their years of practice into ten principles at the core of good couples work. Each principle is illustrated with a clinically compiled case plus personal side-notes and storytelling. Topics addressed include: You know that you need to "treat the relationship," but how are you supposed to get at something as elusive as "a relationship"? ; How do you empathize with both clients if they have opposite points of view? Later on, if they end up separating does that mean you've failed? Are you only successful if you keep couples together? ; Compared to an individual client, a relationship is an entirely different animal. What should you do first? What should you look for? What questions should you ask? If clients give different answers, who should you believe? ; What are you supposed to do with all the emotional and personal history that your clients stir up in you? ; How can you make your work research-based? No one who works with couples will want to be without the insight, guidance, and strategies offered in this book. (Publisher)
Facing the gauntlet -- The first principle : use research-based methods to treat couples -- The second principle : assess first, then decide on treatment -- The third principle : understand each partner's inner world -- The fourth principle : map your treatment route -- The fifth principle : soothe yourself, then intervene -- The sixth principle : process past regrettable incidents -- The seventh principle : replace the four horsemen with gentle conflict management skills -- The eighth principle : strengthen friendship and intimacy -- The ninth principle : suspend moral judgment when treating affairs -- The tenth principle : dive deep to create shared meaning -- Hold the hope
"A Norton professional book."
Includes bibliographical references and index
Keywords: Couples therapy; Counseling; Therapist and patient; Marital Therapy -- methods; Couples Therapy -- methods; Professional-Patient Relations